Limetown : a novel - Akers, Zack; Bronkie, Skip; Smith, Cote, 1982- (Simon & Schuster, 2018)
When three hundred people simply vanish from a research facility in Limetown, seventeen-year-old Lia Haddock discovers that her uncle, Emile Haddock, is among the missing and her parents refuse to discuss what might have happened.